The Role of Problem Solving Approach on Improving Students' Communication Ability and Self Efficacy - Resnawati Resnawati; Utari Sumarmo; Asep Kustiana (IKIP Siliwangi, 2020)
This study is a pretest-posttest experiment control group design having a goal to analyze the role of in problem-solving approach (PSA) on students' mathematical communication ability (MCA) and self-efficacy in mathematics (MSE). The study involves 66 eighth grade students, and MCA test, and an MSE scale. The study revealed that PSA took a better role than SA in obtaining MCA and MSE. Students getting treatment with PSA obtained MCA and MSE were at good grade quality, while students taught by SA attained MCA and MSE were at pretty good grade level. Besides that, the study found there was a very high association between MCA and MSE. Like that, students expressed a positive opinion on PSA, even if, students still realized a few difficulties in solving MCA. Keywords: mathematical communication, self-efficacy, problem-solving approach